Evaluating Academic Supervision Programs in Early Childhood Education: A Case Study of TK Al-Alif in Indonesia - Yunus, Yunus; Rahmatullah, Mamat (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aims to assess how well the Academic Supervision Program is being implemented in the Early Childhood Education (ECE) curriculum. The study employs a qualitative research methodology and concentrates on the assessment process's planning, formative, summative, and procedural phases. This approach is applied to assess the program at TK Al-Alif in Tokke Village, Malangke Subdistrict, Luwu Utara Regency. The findings reveal that the academic supervision conducted by the head of TK Al-Alif includes (a) understanding the concepts, principles, and foundational theories of creative and innovative learning, (b) guiding teachers in developing syllabi for each developmental domain, (c) assisting teachers in selecting and utilizing strategies to enhance students' diverse potentials, (d) mentoring teachers in implementing practical learning activities, and (e) supporting teachers in managing and utilizing technology to expand their knowledge. Additionally, the supervision program employs a mentoring method, which effectively addresses teachers' challenges and proves to be a suitable strategy for improving learning quality. The evaluation of the academic supervision program encompasses (a) context evaluation, (b) input evaluation, (c) process evaluation, and (d) product evaluation. The impact of this supervision is reflected in enhanced teacher creativity, with detailed planning that includes setting objectives, identifying targets, organizing activities, and scheduling supervision timelines.